Mowgli and Baloo - Patel, Raju; McLachlan,Duncan (USA : Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN [distributor])
In the company of his extended family, Mowgli enjoys the jungle life of climbing trees, swinging from vines, bathing with elephants and capturing big black beetles for breakfast
Executive producer, Sharad Patel, Mark Damon ; screenplay, Bayard Johnson
Cast : Donald Pemrick, Dean Fronk, Jo Gilbert
Keywords: Animal films; Animals in motion pictures; Wildlife films